E-LEARNING PENGANTAR STATISTIKA PENDIDIKAN BERBASIS WEB UNTUK MENINGKATKAN HASIL BELAJAR MAHASISWA PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN FAKULTAS ILMU SOSIAL UNIVERSITAS NEGERI JAKARTA - Raharjo Raharjo (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2013)
This study aims to produce an e-learning on course introduction of Statistics Education in Civics Education Department, Faculty of Social Sciences State University of Jakarta. The research method used is a Research and Development ( R & D ) that produces a product by building a web-based e–learning. The subjects of this study were students participating in the course introduction of Statistics Education. The results showed that through the use of e -learning system has give more time and opportunity for students to download or upload informations in the form of text, images , audio and video. The students also can discussions about aspects related to teaching introduction statistics education. Additionally, student learning outcomes on course introduction of statistics education increased. It can be seen from the results of their learning introduction of statistics education before using e-lerarning which â€‹â€‹obtained 67.1 and after the use of e-learning increased to 80.4. And based on the due diligence / quality website http://statistikapendidikan.com obtained average rate of 4.03 to the category of Good.